The role of diet in cancer: the epidemiologic link - Magdalena Stepien; Veronique Chajes; Isabelle Romieu (Instituto Nacional de Salud Pública, 2016)
Diet is an important modifiable risk factor for cancer. Adequate diet modification may play a key role in reducing the incidence of some cancers. A growing body of epidemiological evidence suggested links of some nutritional exposures with individual cancers. This review updates and summarises the existing data on diet related factors for cancer prevention, evaluated in 2007 by World Cancer Research Fund/American Institute for Cancer Research and identifies the areas where more research is needed. Mechanisms of action of nutrients are discussed. For cancer prevention, more apparent association pertains to the role of foods from plant origin, processed meat products and alcohol. There is a lack of evidence to clarify the relationship of dairy and cereal products, different types of carbohydrates, micronutrients naturally found in foods vs supplements, industrial trans-fats, food preparation and handling techniques and dietary patterns and cancer, in order to implement safe cancer prevention strategies.   DOI: http://dx.doi.org/10.21149/spm.v58i2.7795